Blue lightning [videorecording (DVD)] - Williams, Aaron L.; Aaron, Quinton, 1984-; Metallo, Ava; Danniels, Gordon (Green Apple Entertainment, 2024)
A grumpy; old man's life is turned upside down when he discovers a mischievous; young orphan is the daughter of his long-estranged son. Struggling to find common ground; they bond over the town sport of soap box derby racing.